THE AUTONOMOUS WORK IN THE ENGLISH LANGUAGE LEARNING IN 8TH SEMESTER “B” IN LANGUAGE CAREER AT THE UNIVERSIDAD NACIONAL DE CHIMBORAZO IN ACADEMIC PERIOD FROM MARCH 2015 TO AUGUST 2015 - Chinlli Yumisaca, Karina Elizabeth (2016)
This research project describes how students of eighth semester “B” of the school of languages at the National University of Chimborazo develop the Autonomous assignment for English Language learning. A survey of eleven closed questions was applied, each with for items related to the two variables in order to gather information related to how the students proceed with the autonomous assignment. Additionally, an observation guide was carried for three months with contains Meta – cognitive and emotional indicator strategies which who help to determine how students carry out the autonomous project. After applying the survey an observation guide, the analysis and interpretation of results was performed, this describes the activities perform by every students in the learning process